Compound calcium magnesium carbonate vitamin D3 composition and preparation method thereof

By rationally proportioning calcium carbonate and magnesium carbonate, along with antioxidants and suitable excipients, and employing gradient shear speed and fluidized bed granulation technology, the problems of insufficient vitamin D3 stability and uneven mixing in the compound calcium carbonate magnesium vitamin D3 composition were solved, thereby improving the synergistic absorption efficiency of calcium and magnesium and the quality of tablets.

CN121465263APending Publication Date: 2026-02-06HUBEI XINZEFEI PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511734057.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

In existing compound calcium carbonate magnesium vitamin D3 compositions, the problems of insufficient vitamin D3 stability, low calcium-magnesium synergistic absorption efficiency, and uneven mixing have not been effectively solved, affecting the content of active ingredients and tablet forming quality.

Method used

By rationally proportioning calcium carbonate and magnesium carbonate, and combining L-ascorbate palmitate and dl-α-tocopherol acetate for antioxidant effects, along with suitable fillers, binders and other excipients, gradient shear speed and fluidized bed granulation technology are used to ensure uniform mixing and stability of vitamin D3.

Benefits of technology

It achieves improved stability of vitamin D3 in alkaline environments, enhanced synergistic absorption of calcium and magnesium, good tablet hardness and disintegration properties, meets human nutritional needs and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a compound calcium magnesium carbonate and vitamin D3 composition and a preparation method thereof. The composition comprises the following components: calcium carbonate, magnesium carbonate, vitamin D3, L-ascorbyl palmitate, dl-alpha-tocopheryl acetate, a filler, an adhesive, a lubricant, a sweetening agent and a flavoring agent. The vitamin D3 is added in the form of vitamin D3 powder, and the vitamin D3 powder comprises vitamin D3, a stabilizer, an emulsifier, a solvent, a matrix and a carrier. The reasonable proportion of calcium carbonate and magnesium carbonate is defined, absorption competition of calcium carbonate and magnesium carbonate is reduced, the vitamin D3 is matched to promote the absorption effect, and the calcium and magnesium synergistic supplement effect is improved; l-ascorbyl palmitate and dl-alpha-tocopheryl acetate cooperate to resist oxidation, and the finally prepared tablet is uniform in hardness and good in disintegration performance, can stably supplement calcium, magnesium and vitamin D3, and meets the nutritional requirements of human bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vitamin compositions. More specifically, this invention relates to a compound calcium carbonate magnesium vitamin D3 composition and its preparation method. Background Technology

[0002] Mineral nutrients, also known as inorganic salts, comprise dozens of types in the human body. They are categorized into macroelements (calcium, phosphorus, potassium, sodium, chlorine, magnesium, etc.) and microelements (iron, copper, zinc, iodine, selenium, etc.) based on their abundance. Although their total content is relatively low, they play crucial roles. For example, calcium, phosphorus, and magnesium are essential components of bones and teeth and participate in many important physiological processes. Therefore, it is essential to ensure a certain intake of inorganic elements, but attention should be paid to the proper ratio between various elements and appropriate intake methods. Based on this, compound calcium carbonate magnesium vitamin D3 compositions, as common supplements for calcium, magnesium, and vitamin D3, still face several problems and shortcomings in their research and production.

[0003] Firstly, there is the issue of insufficient stability of vitamin D3. Vitamin D3 itself is quite sensitive to light, heat, and oxygen. Calcium carbonate and magnesium carbonate, being alkaline minerals, will make the formulation system alkaline. This alkaline environment will further accelerate the degradation of vitamin D3, leading to a continuous decrease in the content of the active ingredient during storage. Simultaneously, traditional technologies lack specific stabilization solutions for this complex system. Commonly used stabilizers either have limited effectiveness when used alone or have compatibility issues with other components, making it difficult to achieve a synergistic protective effect. This makes solving the vitamin D3 stability problem a challenge in simultaneously achieving both effective stabilization and ensuring component compatibility. Secondly, there is the problem of low synergistic absorption efficiency of calcium and magnesium. In traditional compound preparations, the ratio of calcium to magnesium is often determined based on experience, without considering the competitive relationship between the two minerals during the body's absorption process. Either the calcium content is too high, inhibiting magnesium absorption, or the magnesium content is inappropriate, affecting calcium utilization, resulting in the two minerals failing to fully exert their synergistic supplementation effect. Furthermore, vitamin D3, a key component for promoting calcium and magnesium absorption, is often insufficient due to its poor stability, further reducing the overall absorption efficiency of calcium and magnesium. When adjusting the calcium-magnesium ratio to improve the synergistic absorption effect, improper ratios can easily lead to new formulation stability problems, creating a dilemma. Furthermore, during the mixing process, vitamin D3 powder, due to its small dosage and tendency to agglomerate, is difficult to mix evenly with the large amount of calcium and magnesium granules using traditional mixing methods, resulting in significant deviations in vitamin D3 content in the tablets. Extending the mixing time to improve uniformity can cause granule breakage, affecting tablet forming quality, making it difficult to reconcile mixing uniformity with granule integrity. Summary of the Invention

[0004] To achieve these objectives and other advantages according to the present invention, one technical solution of the present invention provides a compound calcium carbonate magnesium vitamin D3 composition, comprising the following components by weight: Calcium carbonate 760-765 parts, magnesium carbonate 58-60 parts, vitamin D3 0.004-0.006 parts, L-ascorbate palmitate 0-15 parts, dl-α-tocopherol acetate 0-30 parts, filler 35-350 parts, binder 15-115 parts, lubricant 5-20 parts, sweetener 0-3 parts, and flavoring agent 0-10 parts; The vitamin D3 is added in the form of vitamin D3 powder, which, in addition to 0.004 to 0.006 parts of vitamin D3, also includes 2 to 20 parts of stabilizer, 0.5 to 20 parts of emulsifier, 10 to 50 parts of solvent, 20 to 100 parts of matrix and 20 to 200 parts of carrier.

[0005] Preferably, the product comprises, by weight, the following components: 760-765 parts calcium carbonate, 58-60 parts magnesium carbonate, 0.004-0.006 parts vitamin D3, 8-15 parts L-ascorbic acid palmitate, 12-30 parts dl-α-tocopherol acetate, 35-350 parts filler, 15-115 parts binder, 5-20 parts lubricant, 0-3 parts sweetener, and 0-10 parts flavoring agent; The vitamin D3 is added in the form of vitamin D3 powder, which includes 0.004 to 0.006 parts of vitamin D3, 2 to 20 parts of stabilizer, 0.5 to 20 parts of emulsifier, 10 to 50 parts of solvent, 20 to 100 parts of matrix and 20 to 200 parts of carrier.

[0006] By clearly defining the weight range of each component, and combining L-ascorbate palmitate and dl-α-tocopheryl acetate for antioxidant effects, the degradation of vitamin D3 is effectively inhibited, maintaining the content of the active ingredient. A reasonable calcium-magnesium ratio reduces absorption competition and enhances the synergistic effect of vitamin D3. Appropriate fillers, binders, and other excipients resolve mixing inconsistencies, ensuring tablet hardness and disintegration properties. The formulation stably supplements calcium, magnesium, and vitamin D3, meeting the body's nutritional needs and is suitable for industrial production. This solution addresses the problem of reduced active ingredient content in compound calcium carbonate magnesium vitamin D3 compositions, where vitamin D3 is sensitive to light, heat, and oxygen and easily degraded by the alkaline environment of calcium and magnesium. It also resolves absorption competition and the difficulty in achieving the vitamin D3 absorption-promoting effect caused by an unreasonable calcium-magnesium ratio, as well as mixing inconsistencies and poor tablet forming quality due to the high density of calcium and magnesium and poor compatibility with excipients.

[0007] Among them, the hydrophobic palmitic acid chain in L-ascorbic acid palmitate can directly form a dense hydrophobic film on the surface of calcium carbonate particles, reducing the adsorption of environmental moisture by calcium carbonate from the source. In addition, its antioxidant activity can synergize with antioxidants in vitamin D3 powder (such as sorbitol monolaurate and vitamin E) to enhance the inhibition of water-induced vitamin D3 oxidation and avoid the failure problem when antioxidants are used alone. dl-α-tocopherol acetate can combine with the hydroxyl groups on the surface of magnesium carbonate, neutralizing the weak hydrophilicity of magnesium carbonate and reducing the aggregation of water between magnesium carbonate particles. At the same time, its fat-soluble properties can form a stable dispersion system with vitamin D3 in the oil phase, preventing vitamin D3 from being hydrolyzed by water penetration from the oil phase.

[0008] Preferably, the product comprises, by weight, the following components: 762.5 parts calcium carbonate, 59.2 parts magnesium carbonate, 0.005 parts vitamin D3, 9 parts L-ascorbyl palmitate, 13 parts dl-α-tocopherol acetate, 35-350 parts filler, 15-115 parts binder, 5-20 parts lubricant, 0-3 parts sweetener, and 0-10 parts flavoring agent.

[0009] Preferably, the carrier is talc; the filler is selected from sorbitol and microcrystalline cellulose; the binder is povidone or hydroxypropyl cellulose; the lubricant is magnesium stearate or sodium stearate fumarate; the sweetener is aspartame; the flavoring agent is flavoring; the emulsifier is glycerol fatty acid ester; the solvent is medium-chain fatty acid triglyceride; and the matrix is ​​sucrose.

[0010] The high compatibility of various excipients further ensures the quality of the formulation, balancing nutritional supplementation effects with user experience.

[0011] Preferably, the stabilizer comprises, by weight, the following components: 1-8 parts of sorbitol monolaurate, 0.5-5 parts of vitamin E, and 0.5-3 parts of butylated hydroxytoluene; wherein the weight ratio of vitamin E to butylated hydroxytoluene is (1-2):1; Sorbitol monolaurate, through its hydrophilic and lipophilic groups in its molecular structure, achieves emulsification and dispersion by reducing interfacial tension, ensuring a uniform distribution of vitamin E and butylated hydroxytoluene (BHT) within the system. This avoids antioxidant blind spots caused by localized concentration imbalances, laying a uniform environmental foundation for subsequent antioxidant effects. Vitamin E, as a chain-terminating antioxidant, can capture free radicals generated by vitamin D3 oxidation, interrupting the oxidation reaction chain. Meanwhile, BHT, as a hydrogen donor antioxidant, can provide hydrogen atoms to vitamin E free radical intermediates, regenerating them into an active state, forming a relay antioxidant mechanism of "termination-regeneration," significantly improving antioxidant efficiency. Simultaneously, the 1-2:1 ratio of vitamin E to BHT ensures a match in their efficiencies, avoiding both the accumulation of free radical intermediates due to excessive vitamin E and the impact of insufficient BHT on regeneration. Furthermore, the controlled dosage of all three components within a reasonable range eliminates the risk of impurities introduced by excessive raw materials, achieving a balance between antioxidant properties and safety. On the other hand, a method for preparing the aforementioned compound calcium carbonate magnesium vitamin D3 composition is also provided, comprising the following steps: Step 1: Particle Preparation Calcium carbonate, magnesium carbonate, filler, binder and wetting agent are wet granulated to form a soft material, which is then dried at 60~70℃ for 2~3 hours to ensure that the moisture content of the particles is ≤1.0% and then granulated to obtain mixed calcium and magnesium carbonate particles.

[0012] Step Two: Two-Phase Preparation Vitamin D3, stabilizer, L-ascorbyl palmitate, dl-α-tocopherol acetate, emulsifier and solvent are mixed at 60-85℃ to form an oil phase, and simultaneously the matrix and water are mixed and dissolved at 60-85℃ to form an aqueous phase, wherein the weight ratio of matrix to water is 1:2. Step 3: Emulsion Formation First, the aqueous phase is subjected to high-speed shear emulsification at a speed of 2000~2500 r / min, then the oil phase is added and shear emulsification is continued at a speed of 2500~3000 r / min to obtain vitamin D3 emulsion; Step 4: Powder Manufacturing Vitamin D3 powder was prepared by combining vitamin D3 emulsion and carrier using fluidized bed granulation technology. Step 5: Tablet compression molding Vitamin D3 powder was added to mixed calcium and magnesium granules in equal and stepwise amounts. Sweeteners, flavoring agents and lubricants were then added and mixed evenly before being compressed into tablets to finally produce compound calcium carbonate and magnesium vitamin D3 tablets.

[0013] In the granulation stage, high-purity calcium carbonate and magnesium carbonate reduce the interference of impurities on granulation. Sorbitol or microcrystalline cellulose, as fillers, utilize their good flowability and compressibility to reduce inter-granule friction. Combined with a binder, the raw material granules are bonded together through intermolecular forces to form a stable soft material. After drying and granulation, uniformly sized mixed calcium-magnesium granules with the required moisture content are obtained. In the preparation of vitamin D3 emulsion, glycerol fatty acid esters, as emulsifiers, adsorb onto the oil-water interface to form a stable interfacial film, reducing the surface tension of the oil and water phases and ensuring uniform dispersion of the oil phase in the aqueous phase to form an emulsion, preventing stratification. In the fluidized bed granulation stage, talc, as a carrier, utilizes its surface adsorption capacity to ensure uniform adhesion of vitamin D3 emulsion droplets and drying into powder, theoretically ensuring uniform vitamin D3 loading. In the tableting stage, magnesium stearate, as a lubricant, forms a lubricating film on the granule surface, reducing the coefficient of friction between the granules and the equipment and preventing sticking.

[0014] In step three, the aqueous phase pretreatment is performed at a rotation speed of 2000-2500 rpm. This achieves homogenization of the aqueous phase while avoiding excessive turbulence caused by excessive rotation speed, which could introduce a large amount of air. The presence of air could affect the stability of the subsequent emulsion and even accelerate the oxidation of vitamin D3. The rotation speed is increased to 2500-3000 rpm after adding the oil phase because the shear force required for oil phase dispersion is higher than that required for aqueous phase homogenization. If the original rotation speed is maintained after the oil phase is added, the insufficient shear force may result in excessively large oil phase droplets and poor emulsion stability. If a high rotation speed is used for the initial aqueous phase treatment, it will easily lead to energy waste and introduce air, which is detrimental to subsequent operations. This rotation speed gradient setting ensures that the final vitamin D3 emulsion has uniform particle size and high stability, laying a good foundation for subsequent combination with a carrier to produce vitamin D3 powder.

[0015] Preferably, when talc powder is used as the carrier, the following pretreatment is required before use: Pre-dry 100 parts by weight of talc powder at 60~70℃ for 1 hour, and cool for later use; weigh 0.2~1 parts by weight of nano silica and 0.1~0.5 parts by weight of stearic acid, grind them until the particle size is ≤5μm to obtain nano silica-stearic acid material for later use. Add talc powder to a high-speed mixer, stir and disperse, heat to 40~50℃, 1000~1200r / min, and add PDMDAAC ethanol solution dropwise. After the addition is complete, keep warm and stir for 15~20min. The PDMDAAC ethanol solution is obtained by dissolving 0.3~2 parts by weight of PDMDAAC in 5~10 parts by weight of anhydrous ethanol. The weight ratio of talc powder to PDMDAAC ethanol solution is in the range of 100:(5.3~12). Increase the rotation speed to 1800~2200r / min and the temperature to 60~70℃. Add the ground nano-silica-stearic acid material in 3~5 batches, with an interval of 3min between each batch. After adding the material, continue stirring for 20~25min and let it cool naturally to room temperature. Finally, the talc powder was vacuum dried at 80~100℃ and -0.07~-0.08MPa for 1~1.5h, and the moisture content was controlled to be ≤0.5% to obtain the pretreated talc powder.

[0016] Pretreated talc exhibits significantly improved dispersibility, exhibiting no agglomeration when combined with vitamin D3 emulsion, ensuring uniform vitamin D3 content. Improved surface properties enhance compatibility with other excipients, reducing sticking and loose tablets during compression, resulting in more uniform tablet hardness. Nano-silica, with its large specific surface area, adheres to the talc surface through physical adsorption, utilizing its steric hindrance effect to break the van der Waals forces between talc particles, preventing agglomeration and fundamentally improving dispersibility. Stearic acid undergoes esterification with the hydroxyl groups on the talc surface, changing its hydrophilicity to lipophilicity, enhancing its compatibility with fat-soluble vitamin D3 emulsion. PDMDAAC, as a cationic polymer, forms an adsorption layer on the talc surface through electrostatic adsorption, further enhancing steric hindrance and charge repulsion, thus doubly improving dispersion stability. Ultimately, this enhances the carrier's adsorption capacity and dispersibility for vitamin D3 emulsion, while also improving the carrier's chemical stability and reducing subsequent interfacial reactions with calcium and magnesium salts. Furthermore, the amount of raw materials used is controlled at 0.2-1 parts nano-silica, 0.1-0.5 parts stearic acid, and 0.3-2 parts PDMDAAC. This avoids both insufficient dosage failing to improve performance and excessive dosage affecting the load-bearing capacity of talc. Ultimately, the pretreated talc possesses dispersibility, compatibility, and safety, meeting the functional requirements of a carrier.

[0017] Preferably, step four specifically includes: adding a carrier to a fluidized bed, introducing an inert gas, controlling the oxygen content in the fluidized bed to ≤3%, and the inert gas flow rate to be 0.5~1.2 m³ / h, to obtain a fluidized carrier; uniformly spraying vitamin D3 emulsion onto the fluidized carrier, controlling the spray pressure to 0.2~0.3 MPa, and controlling the spray temperature of the vitamin D3 emulsion to 45~55℃, and continuing fluidization for 10~15 min after spraying to obtain vitamin D3 powder.

[0018] Inert gas effectively isolates oxygen, preventing vitamin D3 from oxidizing during granulation and ensuring the content of active ingredients. By precisely controlling the inert gas flow rate, spray pressure, and temperature, vitamin D3 droplets are of suitable size and adhere evenly to the carrier. After drying, the granules are uniform in size, have good flowability, and are free of lumps. When mixed with calcium and magnesium granules, it disperses evenly, ensuring uniform content of active ingredients in the tablets. The process is simple, parameters are easily controlled, making it suitable for industrial-scale mass production, improving production efficiency and product stability.

[0019] An inert gas flow rate of 0.5~1.2 m³ / h is continuously introduced into the fluidized bed to gradually replace the air inside the chamber, ensuring that the oxygen content is stably controlled at ≤3%. If the flow rate is lower than 0.5 m³ / h, the efficiency of inert gas replacing air is too low, which can easily lead to excessive residual oxygen in the chamber, failing to effectively isolate vitamin D3 from oxygen and increasing the risk of oxidative degradation. If the flow rate is higher than 1.2 m³ / h, although it can quickly isolate oxygen, the excessively high airflow will impact the carrier talc powder, disrupting its fluidization state and causing the talc powder particles to collide violently or adhere to the wall, which will negatively affect the subsequent spray adhesion effect. This flow rate, combined with the particle size and density characteristics of talc powder, allows the talc powder particles to be suspended under the action of airflow to form a stable fluidized layer. It avoids insufficient fluidization due to insufficient flow rate and excessive fluidization due to excessive flow rate, laying the foundation for uniform adhesion of vitamin D3 emulsion.

[0020] When the oxygen content exceeds 3%, the oxygen concentration in the system is sufficient to support the continuous oxidation reaction. Especially during the granulation process, the surface area of ​​the particles in contact with oxygen is large, and the oxidation rate will be significantly accelerated, leading to a decrease in vitamin D3 content. When the oxygen content is ≤3%, the oxygen concentration is reduced to a level that is insufficient to initiate a large-scale oxidation reaction, thus inhibiting oxidative degradation from the source.

[0021] Preferably, in step four, when the vitamin D3 emulsion is uniformly sprayed onto the fluidized carrier, the spray nozzle is positioned in the middle region of the fluidized layer of the carrier within the fluidized bed, and the spray nozzle adopts a 45° downward spray angle. An annular airflow distributor is installed above the fluidized layer of the carrier within the fluidized bed, and an auxiliary airflow consistent with the inert gas is introduced. The flow rate of the auxiliary airflow is 0.1~0.2 m³ / h, and the airflow direction is tangential to the fluidization trajectory of the carrier. At the same time, the fluidization speed of the carrier is controlled to be 120~150 r / min by adjusting the rotation speed of the fluidized bed, so that the carrier forms a stable annular fluidization trajectory, ensuring that the vitamin D3 emulsion droplets can be uniformly sprayed onto the carrier surface.

[0022] The spray nozzle is positioned in the middle of the fluidized bed and tilted downwards at a 45° angle. Utilizing the uniform particle distribution in the middle of the fluidized bed, combined with gravity, this allows the vitamin D3 emulsion droplets to be sprayed more precisely onto the carrier particles, improving the contact efficiency between the droplets and the carrier. An annular airflow distributor introduces tangential auxiliary airflow, altering the airflow trajectory within the fluidized bed to create a stable annular fluidized motion for the carrier particles. The centrifugal and shear forces of the fluid further promote thorough mixing of particles and droplets, theoretically preventing droplet aggregation caused by localized particle retention. Simultaneously, the narrow particle size distribution of the talc carrier ensures consistent velocity during annular fluidization, avoiding uneven fluidization due to particle size differences. Combined with the emulsion stability maintained by the emulsifier, this ensures consistently uniform droplet size.

[0023] Preferably, step five includes: Vitamin D3 powder is added to the mixed calcium and magnesium granules in equal amounts in steps. After each addition, the mixture is mixed for 5 minutes using a three-dimensional mixer until all the powder is added. Finally, the powder is added to a blender, followed by the flavoring agent. The mixture is then stirred for 15 minutes, and finally, the lubricant is added and mixed for 3 minutes.

[0024] Vitamin D3 powder is added in equal, stepwise amounts, typically 3-5 times. By gradually increasing the concentration of small amounts of material, the diffusion and convection of particles during mixing prevent excessively high local concentrations caused by a single addition, thus improving mixing uniformity. Subsequent additions of sweeteners, flavoring agents, and lubricants are made from easily dispersible powdered raw materials with particle sizes similar to the mixed calcium and magnesium particles. Under the action of a mixer, these particles quickly achieve uniform dispersion through collision and friction.

[0025] Preferably, in step two, during the oil phase mixing process, an inert gas is simultaneously introduced for protection, with the inert gas flow rate controlled at 0.1~0.3 m³ / h. L-ascorbate palmitate and dl-α-tocopherol acetate are added in stages: first, 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is stirred at 60~65°C for 10~15 min. Then, the remaining 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is heated to 70~85°C and stirred for another 15~20 min to obtain the oil phase.

[0026] L-Ascorbyl Palmitate and dl-α-Tocopheryl Acetate are added in stages, taking advantage of the difference in solubility of the raw materials at different temperatures. First, 50% is added at 60-65℃ to allow the raw materials to initially dissolve and adapt to the system environment; the remaining 50% is added at 70-85℃, using the increased temperature to enhance solvent solubility and ensure complete dissolution of the raw materials. This avoids precipitation caused by insufficient solubility due to a single addition. Medium-chain triglycerides are used as a solvent, utilizing their high solubility for fat-soluble components to provide a good dissolution environment for the two antioxidant raw materials, ensuring uniform composition of the oil phase. Simultaneously, the continuous introduction of inert gas replaces air in the oil phase preparation system, effectively isolating oxygen and preventing the antioxidant raw materials from oxidizing and deteriorating, thus ensuring their activity. Ultimately, this results in a stable and uniform oil phase composition, providing high-quality raw materials for subsequent emulsion preparation.

[0027] The present invention has at least the following beneficial effects: This invention clarifies the optimal ratio of calcium carbonate and magnesium carbonate to reduce their absorption competition. Combined with the absorption-promoting effect of vitamin D3, it enhances the synergistic supplementation effect of calcium and magnesium. L-ascorbic acid palmitate and dl-α-tocopheryl acetate work synergistically for antioxidant effects, and the antioxidant mechanism is further strengthened by stabilizers containing vitamin E and butylated hydroxytoluene, significantly inhibiting the degradation of vitamin D3 in alkaline environments and ensuring stable content of active ingredients. During preparation, wet granulation controls the particle moisture content to ≤1.0%, ensuring uniform calcium and magnesium particle size. Gradient shear speed is used in the emulsion formation stage to avoid air introduction and improve the stability of the vitamin D3 emulsion. Fluidized bed granulation combined with pretreated talc powder achieves efficient encapsulation and uniform loading of vitamin D3 powder. The final tablets have uniform hardness and good disintegration properties, stably supplementing calcium, magnesium, and vitamin D3 to meet the body's nutritional needs.

[0028] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.

[0030] The following description is intended to disclose the present invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious modifications will occur to those skilled in the art. The basic principles of the invention defined in the following description can be applied to other embodiments, modifications, improvements, equivalents, and other technical solutions that do not depart from the spirit and scope of the invention. Example 1

[0031] A compound calcium carbonate magnesium vitamin D3 composition, comprising the following components by weight: 760 parts calcium carbonate, 58 parts magnesium carbonate, 0.004 parts vitamin D3, 8 parts L-ascorbyl palmitate, 12 parts dl-α-tocopherol acetate, 35 parts filler, 15 parts binder, 5 parts lubricant, 1 part sweetener and 1 part flavoring agent. 2 parts stabilizer, 0.5 parts emulsifier, 10 parts solvent, 20 parts matrix and 20 parts carrier.

[0032] Preparation process: Step 1: Particle Preparation Calcium carbonate, magnesium carbonate, filler, binder and wetting agent are wet granulated to form a soft material, which is then dried at 60~70℃ for 2~3 hours to ensure that the moisture content of the particles is ≤1.0% and then granulated to obtain mixed calcium-magnesium granules of calcium carbonate and magnesium carbonate; here, the wetting agent is 50 parts, which is water.

[0033] Step Two: Two-Phase Preparation Vitamin D3, stabilizer, L-ascorbyl palmitate, dl-α-tocopherol acetate, emulsifier and solvent are mixed at 60-85℃ to form an oil phase, and simultaneously the matrix and water are mixed and dissolved at 60-85℃ to form an aqueous phase, wherein the weight ratio of matrix to water is 1:2. In step two, during the oil phase mixing process, an inert gas is simultaneously introduced for protection, with the inert gas flow rate controlled at 0.1~0.3 m³ / h. L-ascorbate palmitate and dl-α-tocopherol acetate are added in stages: first, 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is stirred at 60~65℃ for 10~15 min. Then, the remaining 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is heated to 70~85℃ and stirred for another 15~20 min to obtain the oil phase.

[0034] Step 3: Emulsion Formation First, the aqueous phase is subjected to high-speed shear emulsification at a speed of 2000~2500 r / min, then the oil phase is added and shear emulsification is continued at a speed of 2500~3000 r / min to obtain vitamin D3 emulsion; Step 4: Powder Manufacturing The carrier is added to a fluidized bed, and an inert gas is introduced to control the oxygen content in the fluidized bed to ≤3%. The inert gas flow rate is 0.5~1.2 m³ / h to obtain a fluidized carrier. Vitamin D3 emulsion is evenly sprayed onto the fluidized carrier, with the spray pressure controlled at 0.2~0.3 MPa and the spray temperature of vitamin D3 emulsion controlled at 45~55℃. After spraying, fluidization is continued for 10~15 min to obtain vitamin D3 powder.

[0035] In this process, when the vitamin D3 emulsion is uniformly sprayed onto the fluidized carrier, the spray nozzle is positioned in the middle region of the carrier fluidized layer within the fluidized bed, and the spray nozzle adopts a 45° downward spray angle. An annular airflow distributor is installed above the carrier fluidized layer within the fluidized bed, and an auxiliary airflow consistent with the inert gas is introduced. The flow rate of the auxiliary airflow is 0.1~0.2 m³ / h, and the airflow direction is tangential to the carrier fluidization trajectory. Simultaneously, the fluidization speed of the carrier is controlled to be 120~150 r / min by adjusting the rotation speed of the fluidized bed, so that the carrier forms a stable annular fluidization trajectory, ensuring that the vitamin D3 emulsion droplets can be uniformly sprayed onto the carrier surface.

[0036] Step 5: Tablet compression molding Vitamin D3 powder is added to the mixed calcium and magnesium granules in three equal parts. After each addition, the mixture is mixed for 5 minutes using a three-dimensional mixer until all the powder is added. Finally, the powder is added to a blender, followed by the flavoring agent. The mixture is then stirred for 15 minutes. Finally, the lubricant is added and the mixture is stirred for 3 minutes.

[0037] When talc powder is used as the carrier, the following pretreatment is required before use: 100 parts by weight of talc powder were pre-dried at 60~70℃ for 1 hour and cooled for later use; 0.2 parts by weight of nano silica and 0.1 parts by weight of stearic acid were weighed and ground until the particle size was ≤5μm to obtain nano silica-stearic acid material for later use. Add talc powder to a high-speed mixer, stir and disperse, heat to 40~50℃, 1000~1200r / min, and add PDMDAAC ethanol solution dropwise. After the addition is complete, keep warm and stir for 15~20min. The PDMDAAC ethanol solution is obtained by dissolving 0.3 parts by weight of PDMDAAC in 5 parts by weight of anhydrous ethanol. The weight ratio of talc powder to PDMDAAC ethanol solution is 100:5.3. Increase the rotation speed to 1800~2200r / min and the temperature to 60~70℃. Add the ground nano-silica-stearic acid material in 3~5 batches, with an interval of 3min between each batch. After adding the material, continue stirring for 20~25min and let it cool naturally to room temperature. Finally, the talc powder was vacuum dried at 80~100℃ and -0.07~-0.08MPa for 1~1.5h, and the moisture content was controlled to be ≤0.5% to obtain the pretreated talc powder. Example 2

[0038] A compound calcium carbonate magnesium vitamin D3 composition, comprising the following components by weight: 750 parts calcium carbonate, 60 parts magnesium carbonate, 0.006 parts vitamin D3, 12 parts L-ascorbyl palmitate, 15 parts dl-α-tocopherol acetate, 100 parts filler, 50 parts binder, 10 parts lubricant, 1 part sweetener and 1 part flavoring agent. 5 parts stabilizer, 5 parts emulsifier, 20 parts solvent, 50 parts matrix and 50 parts carrier.

[0039] Preparation process: Step 1: Particle Preparation Calcium carbonate, magnesium carbonate, filler, binder and wetting agent are wet granulated to form a soft material, which is then dried at 60~70℃ for 2~3 hours to ensure that the moisture content of the particles is ≤1.0% and then granulated to obtain mixed calcium-magnesium granules of calcium carbonate and magnesium carbonate; here, the wetting agent is 80 parts, which is water.

[0040] Step Two: Two-Phase Preparation Vitamin D3, stabilizer, L-ascorbyl palmitate, dl-α-tocopherol acetate, emulsifier and solvent are mixed at 60-85℃ to form an oil phase, and simultaneously the matrix and water are mixed and dissolved at 60-85℃ to form an aqueous phase, wherein the weight ratio of matrix to water is 1:2. In step two, during the oil phase mixing process, an inert gas is simultaneously introduced for protection, with the inert gas flow rate controlled at 0.1~0.3 m³ / h. L-ascorbate palmitate and dl-α-tocopherol acetate are added in stages: first, 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is stirred at 60~65℃ for 10~15 min. Then, the remaining 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is heated to 70~85℃ and stirred for another 15~20 min to obtain the oil phase.

[0041] Step 3: Emulsion Formation First, the aqueous phase is subjected to high-speed shear emulsification at a speed of 2000~2500 r / min, then the oil phase is added and shear emulsification is continued at a speed of 2500~3000 r / min to obtain vitamin D3 emulsion; Step 4: Powder Manufacturing The carrier is added to a fluidized bed, and an inert gas is introduced to control the oxygen content in the fluidized bed to ≤3%. The inert gas flow rate is 0.5~1.2 m³ / h to obtain a fluidized carrier. Vitamin D3 emulsion is evenly sprayed onto the fluidized carrier, with the spray pressure controlled at 0.2~0.3 MPa and the spray temperature of vitamin D3 emulsion controlled at 45~55℃. After spraying, fluidization is continued for 10~15 min to obtain vitamin D3 powder.

[0042] In this process, when the vitamin D3 emulsion is uniformly sprayed onto the fluidized carrier, the spray nozzle is positioned in the middle region of the carrier fluidized layer within the fluidized bed, and the spray nozzle adopts a 45° downward spray angle. An annular airflow distributor is installed above the carrier fluidized layer within the fluidized bed, and an auxiliary airflow consistent with the inert gas is introduced. The flow rate of the auxiliary airflow is 0.1~0.2 m³ / h, and the airflow direction is tangential to the carrier fluidization trajectory. Simultaneously, the fluidization speed of the carrier is controlled to be 120~150 r / min by adjusting the rotation speed of the fluidized bed, so that the carrier forms a stable annular fluidization trajectory, ensuring that the vitamin D3 emulsion droplets can be uniformly sprayed onto the carrier surface.

[0043] Step 5: Tablet compression molding Vitamin D3 powder is added to the mixed calcium and magnesium granules in three equal parts. After each addition, the mixture is mixed for 5 minutes using a three-dimensional mixer until all the powder is added. Finally, the powder is added to a blender, followed by the flavoring agent. The mixture is then stirred for 15 minutes. Finally, the lubricant is added and the mixture is stirred for 3 minutes.

[0044] When talc powder is used as the carrier, the following pretreatment is required before use: 100 parts by weight of talc powder were pre-dried at 60~70℃ for 1 hour and cooled for later use; 0.2 parts by weight of nano silica and 0.1 parts by weight of stearic acid were weighed and ground until the particle size was ≤5μm to obtain nano silica-stearic acid material for later use. Add talc powder to a high-speed mixer, stir and disperse, heat to 40~50℃, 1000~1200r / min, and add PDMDAAC ethanol solution dropwise. After the addition is complete, keep warm and stir for 15~20min. The PDMDAAC ethanol solution is obtained by dissolving 0.3 parts by weight of PDMDAAC in 5 parts by weight of anhydrous ethanol. The weight ratio of talc powder to PDMDAAC ethanol solution is 100:5.3. Increase the rotation speed to 1800~2200r / min and the temperature to 60~70℃. Add the ground nano-silica-stearic acid material in 3~5 batches, with an interval of 3min between each batch. After adding the material, continue stirring for 20~25min and let it cool naturally to room temperature. Finally, the talc powder was vacuum dried at 80~100℃ and -0.07~-0.08MPa for 1~1.5h, and the moisture content was controlled to be ≤0.5% to obtain the pretreated talc powder. Example 3

[0045] A compound calcium carbonate magnesium vitamin D3 composition, comprising the following components by weight: 765 parts calcium carbonate, 60 parts magnesium carbonate, 0.006 parts vitamin D3, 15 parts L-ascorbyl palmitate, 30 parts dl-α-tocopherol acetate, 350 parts filler, 115 parts binder, 20 parts lubricant, 1 part sweetener and 1 part flavoring agent. 20 parts stabilizer, 20 parts emulsifier, 50 parts solvent, 100 parts matrix and 200 parts carrier.

[0046] Preparation process: Step 1: Particle Preparation Calcium carbonate, magnesium carbonate, filler, binder and wetting agent are wet granulated to form a soft material, which is then dried at 60~70℃ for 2~3 hours to ensure that the moisture content of the particles is ≤1.0% and then granulated to obtain mixed calcium-magnesium granules of calcium carbonate and magnesium carbonate; here, the wetting agent is 130 parts, which is water.

[0047] Step Two: Two-Phase Preparation Vitamin D3, stabilizer, L-ascorbyl palmitate, dl-α-tocopherol acetate, emulsifier and solvent are mixed at 60-85℃ to form an oil phase, and simultaneously the matrix and water are mixed and dissolved at 60-85℃ to form an aqueous phase, wherein the weight ratio of matrix to water is 1:2. In step two, during the oil phase mixing process, an inert gas is simultaneously introduced for protection, with the inert gas flow rate controlled at 0.1~0.3 m³ / h. L-ascorbate palmitate and dl-α-tocopherol acetate are added in stages: first, 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is stirred at 60~65℃ for 10~15 min. Then, the remaining 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is heated to 70~85℃ and stirred for another 15~20 min to obtain the oil phase.

[0048] Step 3: Emulsion Formation First, the aqueous phase is subjected to high-speed shear emulsification at a speed of 2000~2500 r / min, then the oil phase is added and shear emulsification is continued at a speed of 2500~3000 r / min to obtain vitamin D3 emulsion; Step 4: Powder Manufacturing The carrier is added to a fluidized bed, and an inert gas is introduced to control the oxygen content in the fluidized bed to ≤3%. The inert gas flow rate is 0.5~1.2 m³ / h to obtain a fluidized carrier. Vitamin D3 emulsion is evenly sprayed onto the fluidized carrier, with the spray pressure controlled at 0.2~0.3 MPa and the spray temperature of vitamin D3 emulsion controlled at 45~55℃. After spraying, fluidization is continued for 10~15 min to obtain vitamin D3 powder.

[0049] In this process, when the vitamin D3 emulsion is uniformly sprayed onto the fluidized carrier, the spray nozzle is positioned in the middle region of the carrier fluidized layer within the fluidized bed, and the spray nozzle adopts a 45° downward spray angle. An annular airflow distributor is installed above the carrier fluidized layer within the fluidized bed, and an auxiliary airflow consistent with the inert gas is introduced. The flow rate of the auxiliary airflow is 0.1~0.2 m³ / h, and the airflow direction is tangential to the carrier fluidization trajectory. Simultaneously, the fluidization speed of the carrier is controlled to be 120~150 r / min by adjusting the rotation speed of the fluidized bed, so that the carrier forms a stable annular fluidization trajectory, ensuring that the vitamin D3 emulsion droplets can be uniformly sprayed onto the carrier surface.

[0050] Step 5: Tablet compression molding Vitamin D3 powder is added to the mixed calcium and magnesium granules in three equal parts. After each addition, the mixture is mixed for 5 minutes using a three-dimensional mixer until all the powder is added. Finally, the powder is added to a blender, followed by the flavoring agent. The mixture is then stirred for 15 minutes. Finally, the lubricant is added and the mixture is stirred for 3 minutes.

[0051] When talc powder is used as the carrier, the following pretreatment is required before use: 100 parts by weight of talc powder were pre-dried at 60~70℃ for 1 hour and cooled for later use; 0.2 parts by weight of nano silica and 0.1 parts by weight of stearic acid were weighed and ground until the particle size was ≤5μm to obtain nano silica-stearic acid material for later use. Add talc powder to a high-speed mixer, stir and disperse, heat to 40~50℃, 1000~1200r / min, and add PDMDAAC ethanol solution dropwise. After the addition is complete, keep warm and stir for 15~20min. The PDMDAAC ethanol solution is obtained by dissolving 0.3 parts by weight of PDMDAAC in 5 parts by weight of anhydrous ethanol. The weight ratio of talc powder to PDMDAAC ethanol solution is 100:5.3. Increase the rotation speed to 1800~2200r / min and the temperature to 60~70℃. Add the ground nano-silica-stearic acid material in 3~5 batches, with an interval of 3min between each batch. After adding the material, continue stirring for 20~25min and let it cool naturally to room temperature. Finally, the talc powder was vacuum dried at 80~100℃ and -0.07~-0.08MPa for 1~1.5h, and the moisture content was controlled to be ≤0.5% to obtain the pretreated talc powder.

[0052] Comparative Example 1: Same as Example 1, except that L-ascorbyl palmitate is not included in the comparative example.

[0053] Comparative Example 2: Same as Example 1, except that the comparative example does not contain dl-α-tocopherol acetate.

[0054] Comparative Example 3: Same as Example 1, except that the stabilizer in the comparative example does not contain butylated hydroxytoluene.

[0055] Comparative Example 4: Same as Example 1, except that the stabilizer in the comparative example does not contain vitamin E.

[0056] Comparative Example 5: Same as Example 1, except that in step three of the comparative example, the rotation speed of both the aqueous phase pretreatment and the oil phase pretreatment is 2500~3000 rpm.

[0057] Comparative Example 6: Same as Example 1, except that the carrier talc powder in the comparative example was not pretreated.

[0058] Experiment 1: Stability Test The tablets containing the compound calcium carbonate magnesium vitamin D3 composition of Examples 1-3 and Comparative Examples 1-6 were stored at a temperature of 60°C, a humidity of 75%, and away from direct sunlight. The degradation rate of vitamin D3 in each tablet was measured at 1 month, 2 months, and 3 months compared to 0 month. The results are shown in Table 1.

[0059] Table 1

[0060] As can be seen from the data in Table 1, the vitamin D3 stability of Examples 1-3 is far superior to that of Comparative Examples 1-6, with a degradation rate of only 1.88%-1.96% after 12 months, while that of Comparative Examples 1-6 is all above 6.22%, reaching a maximum of 7.29% (Comparative Example 6). This is because Examples 1-3 are the result of the synergistic effect of multiple factors. Among them, L-ascorbic acid palmitate forms a hydrophobic film on the surface of calcium carbonate, dl-α-tocopheryl acetate neutralizes the hydrophilicity of magnesium carbonate, and the two form a relay antioxidant mechanism with the stabilizer containing vitamin E and butylated hydroxytoluene; a reasonable rotation speed gradient avoids the introduction of air into the aqueous phase, and pretreated talc tightly wraps the droplets to isolate oxygen and water.

[0061] Comparative Example 1, lacking L-ascorbyl palmitate, cannot form a dense hydrophobic film on the surface of calcium carbonate particles through its hydrophobic palmitic acid chains. This results in the calcium carbonate's ability to adsorb environmental moisture not being suppressed, allowing a large amount of water to easily penetrate into the particles and contact vitamin D3, accelerating vitamin D3 hydrolysis. Furthermore, it loses its antioxidant activity and synergistic effect with the antioxidants in the vitamin D3 powder, failing to enhance the inhibitory effect on water-induced vitamin D3 oxidation, leading to a significant decrease in the overall efficiency of the antioxidant system. The combined effects of water hydrolysis and oxidative degradation resulted in a 4.34% higher degradation rate after 12 months compared to Example 1, indicating a significantly faster degradation rate. Comparative Example 2, lacking dl-α-tocopherol acetate, cannot neutralize the weak hydrophilicity of magnesium carbonate through its binding with the hydroxyl groups on the magnesium carbonate surface. This leads to moisture accumulation between magnesium carbonate particles under 75% humidity conditions, creating a localized high-humidity environment that accelerates vitamin D3 hydrolysis. Furthermore, it loses its fat-soluble properties and synergistic effect with vitamin D3 in the oil phase. Without dl-α-tocopherol acetate, vitamin D3 cannot form a stable dispersion system in the oil phase, making it prone to oil-water separation due to moisture penetration. This further increases the probability of vitamin D3 contacting water, and the decreased stability of the oil phase also exacerbates the oxidation risk of vitamin D3. The combined effects of hydrolysis and oxidation result in a 5.23% higher degradation rate after 12 months compared to Example 1, indicating a significantly accelerated degradation. The stabilizer in Comparative Example 3 did not contain butylated hydroxytoluene. The free radical intermediates formed after vitamin E captures free radicals could not obtain hydrogen atoms to regenerate into an active state, resulting in the breakage of the antioxidant chain. As active vitamin E continued to be consumed, it became difficult to sustain oxidation inhibition. The degradation rate after 12 months was 5.11% higher than in Example 1, and the oxidation reaction intensified over time. The stabilizer in Comparative Example 4 did not contain vitamin E, thus lacking a chain-terminating antioxidant. Free radicals generated by vitamin D3 oxidation could not be captured in time, leading to a continuous extension of the oxidation reaction chain and the oxidative destruction of a large number of vitamin D3 molecules. The degradation rate after 12 months was 4.88% higher than in Example 1, and the degradation process lacked an effective blocking mechanism. Comparative Example 5 did not use a speed gradient; both the aqueous phase pretreatment and oil phase shearing were performed at high speeds of 2500-3000 r / min, resulting in excessive turbulence in the aqueous phase and the introduction of a large amount of air. The emulsion formed a gas-oil-water three-phase mixed system, with oxygen directly contacting vitamin D3. The degradation rate after 12 months was 5.24% higher than in Example 1, with oxygen acting as a key oxidation factor that significantly accelerated degradation. The talc powder in Comparative Example 6 was not pretreated, and the surface retained moisture and was prone to agglomeration. During storage, moisture continued to penetrate into vitamin D3, and the gaps between the agglomerated particles provided channels for oxygen, keeping vitamin D3 in an easily oxidized environment for a long time. The degradation rate after 12 months was 5.41% higher than that in Example 1, making it the group with the most severe degradation among all groups.

[0062] Experiment 2: Uniformity of Vitamin D3 Content Content uniformity assessment: Table 2 Group Content uniformity (%) / limit A+2.2S≤15 Example 1 4 Example 2 3 Example 3 3 Comparative Example 1 18 Comparative Example 2 20 Comparative Example 3 21 Comparative Example 4 18 Comparative Example 5 19 Comparative Example 6 22 As can be seen from the data in Table 2, the content uniformity of Examples 1-3 was 3-4, far below the limit of ≤15, while that of Comparative Examples 1-6 was all above 18, with the highest reaching 22 (Comparative Example 6). The examples used suitable excipients (sorbitol / microcrystalline cellulose, povidone / hydroxypropyl cellulose) to prepare uniform calcium and magnesium particles. Stable vitamin D3 emulsion combined with pretreated talc powder formed a free-flowing vitamin D3 powder, which was uniformly dispersed through stepwise addition in equal amounts and three-dimensional mixing. Furthermore, L-ascorbic acid palmitate and dl-α-tocopheryl acetate improved the surface properties of the calcium and magnesium particles, preventing agglomeration.

[0063] Comparative Example 1 lacks L-ascorbyl palmitate. Due to the lack of a hydrophobic film protecting its surface, the calcium carbonate particles easily agglomerate, forming clumps. Vitamin D3 powder (only 0.004 parts) has difficulty penetrating into these clumps and can only accumulate between them. This results in some areas of the tablet having excessively high vitamin D3 concentrations while others have excessively low concentrations. The content uniformity is 14 higher than in Example 1, exceeding the acceptable limit. Comparative Example 2 lacks dl-α-tocopherol acetate. The magnesium carbonate particles have a strong hydrophilic surface and easily agglomerate into large clumps due to water adsorption when mixed with other ingredients. These clumps hinder the uniform dispersion of vitamin D3 powder, preventing its even distribution throughout the material system. The content uniformity is 16 higher than in Example 1, with significant differences in content across different parts of the tablet. The stabilizer in Comparative Example 3 did not contain butylated hydroxytoluene. The oil phase was easily oxidized during preparation, causing the vitamin D3 emulsion to agglomerate and form coarse particles. The resulting vitamin D3 powder had uneven particle size and was prone to clumping. When mixed with the calcium and magnesium granules, the agglomerated vitamin D3 powder was difficult to disperse, resulting in localized enrichment. The content uniformity was 17% higher than in Example 1, indicating extremely poor uniformity. The stabilizer in Comparative Example 4 did not contain vitamin E. Slight oxidation of the oil phase caused partial agglomeration of the vitamin D3 emulsion, resulting in particle size differences in the resulting vitamin D3 powder, with some fine powder and some coarse particles coexisting. During mixing, the coarse particles, due to their poor flowability, were difficult to fully integrate with the calcium and magnesium granules, leading to uneven content distribution. The content uniformity was 14% higher than in Example 1, failing to meet the acceptable standard. Comparative Example 5 did not employ a rotation speed gradient. The high rotation speed introduced a large number of air bubbles into the aqueous phase. During spray powdering, the vitamin D3 emulsion experienced bubble rupture, resulting in some particles being too large. This led to significant particle size variation in the resulting vitamin D3 powder. The coarse particles easily settled during mixing and could not be uniformly mixed with the calcium and magnesium particles. The content uniformity was 15% higher than in Example 1, indicating significantly insufficient uniformity. In Comparative Example 6, the talc powder was not pretreated and easily agglomerated to form large clumps of 500-1000 μm. After combining with the vitamin D3 emulsion, the vitamin D3 concentration inside the clumps was extremely high, while the concentration outside was extremely low. This resulted in a large variation in the particle size of the resulting vitamin D3 powder. The large clumps could not be dispersed during mixing, leading to drastic fluctuations in the vitamin D3 content in the tablets. The content uniformity was 18% higher than in Example 1, making it the group with the worst uniformity.

[0064] Experiment 3: Encapsulation efficiency assessment Table 3 Group Encapsulation rate Example 1 99.92% Example 2 99.76% Example 3 99.05% Comparative Example 1 89% Comparative Example 2 91% Comparative Example 3 87% Comparative Example 4 92% Comparative Example 5 84% Comparative Example 6 79% As can be seen from the data in Table 3, the encapsulation efficiency of Examples 1-3 reached 99.05%-99.92%, approaching complete encapsulation, while Comparative Examples 1-6 were all below 92%. Examples 1-3, through a reasonable rotation speed gradient and inert gas protection, ensured uniform vitamin D3 droplets (1-5 μm) without agglomeration or bubbles; the pretreated talc powder exhibited good dispersibility, strong lipophilicity, and a large adsorption area; and the precise spraying process (spray nozzle position, angle, and auxiliary airflow) ensured uniform adhesion of the droplets to the carrier, achieving efficient encapsulation.

[0065] Comparative Example 1, lacking L-ascorbyl palmitate, resulted in decreased stability of the vitamin D3 emulsion due to the loss of its stabilizing effect. Some droplets agglomerated into larger particles during preparation, exceeding the adsorption capacity of the talc carrier and failing to be effectively captured. Unadsorbed droplets were lost or settled with the airflow, leading to an encapsulation rate 10.92% lower than Example 1, and a significant reduction in encapsulation efficiency. Comparative Example 2, lacking dl-α-tocopherol acetate, exhibited poorer oil phase stability. During storage and spraying, some vitamin D3 precipitated, forming fine crystals. These crystals could not effectively bind with the talc carrier, directly causing vitamin D3 loss. The encapsulation rate was 8.92% lower than Example 1, indicating loss of effective components during the encapsulation process.

[0066] In Comparative Example 3, the stabilizer did not contain butylated hydroxytoluene. Oxidation in the oil phase caused a large agglomeration of the vitamin D3 emulsion, forming large particles. These large droplets had a diameter far exceeding the adsorption threshold of the carrier talc, making them unable to adhere to the carrier surface. They could only escape with the inert airflow or settle to the bottom of the fluidized bed. The number of unencapsulated droplets was high, and the encapsulation rate was 12.92% lower than in Example 1, resulting in significant encapsulation loss. In Comparative Example 4, the stabilizer did not contain vitamin E. Slight oxidation in the oil phase caused a small amount of vitamin D3 emulsion to agglomerate. While some of the small agglomerated particles could be adsorbed by the carrier, a small number remained uncaptured due to their slightly larger size. The number of unencapsulated droplets was lower, and the encapsulation rate was 7.92% lower than in Example 1, resulting in relatively smaller encapsulation loss. Comparative Example 5 did not employ a rotation speed gradient. The high rotation speed introduced a large amount of air into the aqueous phase, resulting in numerous bubbles in the vitamin D3 emulsion. During spraying, the bursting of these bubbles caused some droplets to escape directly with the airflow. Simultaneously, excessive shearing caused some droplets to agglomerate into large particles that could not be adsorbed. These two factors combined led to a large droplet loss. The talc in Comparative Example 6 was not pretreated and had a strong hydrophilic surface, resulting in poor compatibility with the fat-soluble vitamin D3 emulsion. The emulsion droplets could not effectively adhere to the talc surface, and a large number of emulsion droplets settled to the bottom of the fluidized bed due to gravity. This defect in the compatibility between the carrier and the emulsion droplets led to low encapsulation efficiency.

[0067] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and embodiments shown and described herein.

Claims

1. A compound calcium carbonate magnesium vitamin D3 composition, characterized in that, By weight, it contains the following ingredients: Calcium carbonate 760-765 parts, magnesium carbonate 58-60 parts, vitamin D3 0.004-0.006 parts, L-ascorbate palmitate 0-15 parts, dl-α-tocopherol acetate 0-30 parts, filler 35-350 parts, binder 15-115 parts, lubricant 5-20 parts, sweetener 0-3 parts, and flavoring agent 0-10 parts; The vitamin D3 is added in the form of vitamin D3 powder, which includes 0.004 to 0.006 parts of vitamin D3, 2 to 20 parts of stabilizer, 0.5 to 20 parts of emulsifier, 10 to 50 parts of solvent, 20 to 100 parts of matrix and 20 to 200 parts of carrier.

2. The compound calcium carbonate magnesium vitamin D3 composition according to claim 1, characterized in that, By weight, it contains the following ingredients: Calcium carbonate 760-765 parts, magnesium carbonate 58-60 parts, vitamin D3 0.004-0.006 parts, L-ascorbyl palmitate 8-15 parts, dl-α-tocopherol acetate 12-30 parts, filler 35-350 parts, binder 15-115 parts, lubricant 5-20 parts, sweetener 0-3 parts, and flavoring agent 0-10 parts; The vitamin D3 is added in the form of vitamin D3 powder, which includes 0.004 to 0.006 parts of vitamin D3, 2 to 20 parts of stabilizer, 0.5 to 20 parts of emulsifier, 10 to 50 parts of solvent, 20 to 100 parts of matrix and 20 to 200 parts of carrier.

3. The compound calcium carbonate magnesium vitamin D3 composition according to claim 2, characterized in that, The carrier is talc; the filler is selected from sorbitol and microcrystalline cellulose; the binder is povidone or hydroxypropyl cellulose; the lubricant is magnesium stearate or sodium stearate fumarate; the sweetener is aspartame; the flavoring agent is flavoring; the emulsifier is glycerol fatty acid ester; the solvent is medium-chain fatty acid triglyceride; and the matrix is ​​sucrose.

4. The compound calcium carbonate magnesium vitamin D3 composition according to claim 2, characterized in that, The stabilizer, by weight, comprises the following components: 1-8 parts of sorbitol monolaurate, 0.5-5 parts of vitamin E, and 0.5-3 parts of butylated hydroxytoluene; wherein the weight ratio of vitamin E to butylated hydroxytoluene is (1-2):

1.

5. The method for preparing the compound calcium carbonate magnesium vitamin D3 composition according to any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Particle Preparation Calcium carbonate, magnesium carbonate, filler, binder and wetting agent are wet granulated to form a soft material, which is then dried at 60~70℃ for 2~3 hours to ensure that the moisture content of the particles is ≤1.0% and then granulated to obtain mixed calcium and magnesium carbonate particles. Step Two: Two-Phase Preparation Vitamin D3, stabilizer, L-ascorbyl palmitate, dl-α-tocopherol acetate, emulsifier and solvent are mixed at 60-85℃ to form an oil phase, and simultaneously the matrix and water are mixed and dissolved at 60-85℃ to form an aqueous phase, wherein the weight ratio of matrix to water is 1:

2. Step 3: Emulsion Formation First, the aqueous phase is subjected to high-speed shear emulsification at a speed of 2000~2500 r / min, then the oil phase is added and shear emulsification is continued at a speed of 2500~3000 r / min to obtain vitamin D3 emulsion; Step 4: Powder Manufacturing Vitamin D3 powder was prepared by combining vitamin D3 emulsion and carrier using fluidized bed granulation technology. Step 5: Tablet compression molding Vitamin D3 powder was added to mixed calcium and magnesium granules in equal and stepwise amounts. Sweeteners, flavoring agents and lubricants were then added and mixed evenly before being compressed into tablets to finally produce compound calcium carbonate and magnesium vitamin D3 tablets.

6. The compound calcium carbonate magnesium vitamin D3 composition according to claim 5, characterized in that, When talc powder is used as the carrier, the following pretreatment is required before use: 100 parts by weight of talc powder are pre-dried at 60~70℃ for 1 hour and cooled for later use; 0.2~1 parts by weight of nano silica and 0.1~0.5 parts by weight of stearic acid are weighed and ground until the particle size is ≤5μm to obtain nano silica-stearic acid material for later use. Add talc powder to a high-speed mixer, stir and disperse, heat to 40~50℃, 1000~1200r / min, and add PDMDAAC ethanol solution dropwise. After the addition is complete, keep warm and stir for 15~20min. The PDMDAAC ethanol solution is obtained by dissolving 0.3~2 parts by weight of PDMDAAC in 5~10 parts by weight of anhydrous ethanol. The weight ratio of talc powder to PDMDAAC ethanol solution is in the range of 100:(5.3~12). Increase the rotation speed to 1800~2200r / min and the temperature to 60~70℃. Add the ground nano-silica-stearic acid material in 3~5 batches, with an interval of 3min between each batch. After adding the material, continue stirring for 20~25min and let it cool naturally to room temperature. Finally, the talc powder was vacuum dried at 80~100 MPa and -0.07~-0.08 MPa for 1~1.5 h, and the moisture content was controlled to be ≤0.5% to obtain the pretreated talc powder.

7. The method for preparing the compound calcium carbonate magnesium vitamin D3 composition according to claim 5, characterized in that, Step four specifically includes: adding the carrier to a fluidized bed, introducing inert gas, controlling the oxygen content in the fluidized bed to ≤3%, and the inert gas flow rate to 0.5~1.2 m³ / h to obtain a fluidized carrier; uniformly spraying vitamin D3 emulsion onto the fluidized carrier, controlling the spray pressure to 0.2~0.3 MPa, and controlling the spray temperature of the vitamin D3 emulsion to 45~55℃, and continuing fluidization for 10~15 min after spraying to obtain vitamin D3 powder.

8. The method for preparing the compound calcium carbonate magnesium vitamin D3 composition according to claim 7, characterized in that, In step four, when the vitamin D3 emulsion is uniformly sprayed onto the fluidized carrier, the spray nozzle is positioned in the middle region of the carrier fluidized layer within the fluidized bed, and the spray nozzle adopts a 45° downward spray angle. An annular airflow distributor is installed above the carrier fluidized layer within the fluidized bed, and an auxiliary airflow consistent with the inert gas is introduced. The flow rate of the auxiliary airflow is 0.1~0.2 m³ / h, and the airflow direction is tangential to the carrier fluidization trajectory. Simultaneously, the carrier fluidization speed is controlled to 120~150 r / min by adjusting the rotation speed of the fluidized bed, so that the carrier forms a stable annular fluidization trajectory, ensuring that the vitamin D3 emulsion droplets can be uniformly sprayed onto the carrier surface.

9. The method for preparing the compound calcium carbonate magnesium vitamin D3 composition according to claim 5, characterized in that, Step five includes: Vitamin D3 powder is added to the mixed calcium and magnesium granules in equal amounts in steps. After each addition, the mixture is mixed for 5 minutes using a three-dimensional mixer until all the powder is added. Finally, the powder is added to a blender, followed by the flavoring agent. The mixture is then stirred for 15 minutes, and finally, the lubricant is added and mixed for 3 minutes.

10. The method for preparing the compound calcium carbonate magnesium vitamin D3 composition according to claim 5, characterized in that, In step two, during the oil phase mixing process, an inert gas is simultaneously introduced for protection, with the inert gas flow rate controlled at 0.1~0.3 m³ / h. L-ascorbate palmitate and dl-α-tocopherol acetate are added in stages: first, 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is stirred at 60~65℃ for 10~15 min. Then, the remaining 50% by weight of L-ascorbate palmitate and 50% by weight of dl-α-tocopherol acetate are added, and the mixture is heated to 70~85℃ and stirred for another 15~20 min to obtain the oil phase.